Measurement of the average lifetime of B hadrons - Braunschweig, W; Gerhards, R; Kirschfink, F; Martyn, H; Bock, B; Fischer, H; Hartmann, H; Hartmann, J; Hilger, E; Jocksch, A; Wedemeyer, R; Foster, B; et al. (Springer-Verlag, 1989)
The average lifetime of B hadrons has been measured by the TASSO collaboration using 110 pb-1 of data collected in 1986 at a center of mass energy of 35 GeV. Measurements by three different methods are presented and a method of B-enrichment is discussed. The result of the impact parameter method is τB=1.36±0.13±0.28 ps, that of the vertex method is τB=1.30±0.10±0.28 ps and that of the dipole method is τB=1.47±0.14±0.30 ps. These are combined to give the result τB=1.35±0.10±0.24 ps. © 1989 Springer-Verlag.